Dataset on cortisol concentration in hair - Olsen Faresjö, Åshild (Linköping University, 2022)
The content of this dataset is all information month by month (24) about cortisol concentration in hair among 48 women and other relevant questions, like stress, use of steroids, work and so one.

The dataset was originally published in DiVA and moved to SND in 2024.

Se engelsk beskrivning för info.

2023-01-13 Published the data files translated into English.
Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Dataset på kortisolkoncentrationen i hår
Keywords: hydrocortisone; hydrokortison; corticosteroids; kortikosteroider; glucocorticoids; glukokortikoider; hair (head); hår; steroids; steroider; chemical compounds; kemiska föreningar; Biomedical Laboratory Science/Technology; Biomedicinsk laboratorievetenskap/teknologi